2022
DOI: 10.3389/fphar.2022.996757
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of inflammatory biomarkers in aged patients with oral squamous cell carcinoma

Abstract: Background: Better prognostic biomarkers for oral squamous cell carcinoma (OSCC) must be developed, particularly within the realm of clinically and frequently administered tests, to advise appropriate clinical therapy and follow-up. In this study, we retrospectively investigated which of the several inflammation-nutrition indicators might predict the prognosis of patients with OSCC.Methods:  The preoperative neutrophil-lymphocyte ratio (NLR), lymphocyte–monocyte ratio (LMR), platelet–lymphocyte ratio (PLR), CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…They found that a low PNI was associated with shorter OS and DFS in patients with OSCC through multivariate analysis ( 38 ). Although that study did not include SII for analysis in OSCC, their results were important to investigate mechanisms ( 38 ). In peripheral blood analyses, inflammation-related markers were mainly composed of upregulated factors (neutrophils, platelets, monocytes, and CRP) and downregulated factors (lymphocytes, albumin, total cholesterol, and hemoglobin).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that a low PNI was associated with shorter OS and DFS in patients with OSCC through multivariate analysis ( 38 ). Although that study did not include SII for analysis in OSCC, their results were important to investigate mechanisms ( 38 ). In peripheral blood analyses, inflammation-related markers were mainly composed of upregulated factors (neutrophils, platelets, monocytes, and CRP) and downregulated factors (lymphocytes, albumin, total cholesterol, and hemoglobin).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a recent single study by Yoshimura et al investigated the prognostic effect of multiple inflammation-nutrition parameters including NLR, PLR, LMR, CRP-albumin ratio (CAR), Glasgow prognostic score (GPS), modified GPS (mGPS), prognostic nutritional index (PNI), controlling nutrition status (CONUT), and modified CONUT (mCONUT) in patients with OSCC receiving surgery (38). They found that a low PNI was associated with shorter OS and DFS in patients with OSCC through multivariate analysis (38). Although that study did not include SII for analysis in OSCC, their results were important to investigate mechanisms (38).…”
Section: Discussionmentioning
confidence: 99%
“…Speci cally, subtypes of in ammatory bowel disease, such as Crohn's disease and ulcerative colitis, have been linked to this heightened risk. Additionally, various in ammatory markers have been investigated in relation to oral cancer risk [9,10]. Elevated levels of pro-in ammatory factors, including interleukin (IL)-6, IL-27, and tumor necrosis factor (TNF)-α, have been observed in individuals with oral cancer [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Abundant and compelling evidence has demonstrated that inflammation facilitates angiogenesis, tumor invasion and metastasis by supplying bioactive molecules to the tumor environment (9). The cancer-associated systemic inflammatory response has become a critical indicator of tumor progression (10)(11)(12). Subsequently, biomarkers reflecting the level of systemic inflammation blossom, producing a wide range of circulating blood cell count-based inflammatory markers that have helped refine prognosis prediction when incorporated with TNM system in multiple malignancies (13,14).…”
Section: Introductionmentioning
confidence: 99%